2018
DOI: 10.1007/978-3-319-91803-7_2
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Referral and Usage of Science Fiction in HCI Literature

Abstract: Research on science fiction (sci-fi) in scientific publications has indicated the usage of sci-fi stories, movies or shows to inspire novel Human-Computer Interaction (HCI) research. Yet no studies have analysed sci-fi in a top-ranked computer science conference at present. For that reason, we examine the CHI main track for the presence and nature of sci-fi referrals in relationship to HCI research. We search for six sci-fi terms in a dataset of 5812 CHI main proceedings and code the context of 175 sci-fi refe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 45 publications
(39 reference statements)
0
10
0
1
Order By: Relevance
“…The related work provides a thematic literature review and indicates a mutual, yet not quantified, relationship of both fields. The prior work introduces three pilot studies [19,20,21] which confirmed the presence and usage of SF concepts in the ACM Digital Library (DL), respectively the CHI proceedings. To further investigate these suggestions and corroborate RO1, an in-depth study of the occurrence of SF in a larger scientific corpus of peer-reviewed publications is conducted in a comparable collection, that is the IEEE Xplore DL repository.…”
Section: Ro 1: Identify An Interplay Between Sf and Hci Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…The related work provides a thematic literature review and indicates a mutual, yet not quantified, relationship of both fields. The prior work introduces three pilot studies [19,20,21] which confirmed the presence and usage of SF concepts in the ACM Digital Library (DL), respectively the CHI proceedings. To further investigate these suggestions and corroborate RO1, an in-depth study of the occurrence of SF in a larger scientific corpus of peer-reviewed publications is conducted in a comparable collection, that is the IEEE Xplore DL repository.…”
Section: Ro 1: Identify An Interplay Between Sf and Hci Researchmentioning
confidence: 99%
“…In 2017, the first pilot study on Star Trek in the ACM DL was published [19]. In 2018, the second pilot study was published in the context of the 2018 HCII conference [20].…”
Section: Prior Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Esta influencia se da, principalmente, en tres ámbitos: el planteamiento teórico, la exploración de otras formas de interacción entre humanos y máquinas y el estudio acerca de la posibilidad de modificar el cuerpo humano. Además, el asesoramiento con miras a la ciencia ficción en las empresas y laboratorios de investigación cada vez es más común, con el objetivo de crear nuevas máquinas que respondan a un adecuado impacto social (Jordan, Mubin, Obaid, Silva, 2018).…”
Section: Metodologíaunclassified
“…In continuation of recent prior work, for example [33,34], our research methodology is based on content analysis and text mining of the presence of sci-fi-based robots in literature, a technique that emerges from the field of Scientometrics [38]. A similar method also applied by others, for instance de Souza [14], who currently explores the usages of the words and concepts of "human" or "user" within theoretical computer science repositories.…”
Section: Introductionmentioning
confidence: 99%